Involvement of opioid system in antidepressant‐like effect of the cannabinoid CB1 receptor inverse agonist AM‐251 after physical stress in mice. (February 2016) - Ostadhadi, Sattar; Haj‐Mirzaian, Arya; Nikoui, Vahid; Kordjazy, Nastaran; Dehpour, Ahmad‐Reza
Summary: Cannabinoid inverse agonists possess antidepressant‐like properties, but the mechanism of this action is unknown. Numerous studies have reported the interaction between opioid and cannabinoid pathways. In this study, acute foot‐shock stress was used in mice to investigate the involvement of the opioid pathway in the antidepressant‐like effect of the cannabinoid CB1 receptor inverse agonist AM‐251. Stress was induced by intermittent foot‐shock stimulation for 30 min. Then, using the forced swimming test (FST) and tail suspension test (TST), the immobility time was measured. Results show that the immobility time was significantly prolonged in animals subjected to foot‐shock stress, compared with non‐stressed controls ( P < 0.01). Also, the serum corticosterone level was significantly increased after stress induction ( P < 0.001). Administration of AM‐251 (0.5 and 0.3 mg/kg, intraperitoneally (i.p.)), significantly decreased the immobility time of stressed mice in the FST ( P < 0.001 and P < 0.01, respectively) and TST ( P < 0.01 and P < 0.05, respectively). The lowest dose of AM‐251 (0.1 mg/kg), naltrexone (0.3 mg/kg), and morphine (1.0 mg/kg) did not show any significant effect on stressed animals ( P > 0.05). Co‐administration of AM‐251 with sub‐effective dose of naltrexone decreased the effective dose of this cannabinoid inverse agonist, to 0.1 mg/kg ( P < 0.01). On the other hand, administration of the sub‐effective dose of morphine reversed the anti‐immobility effect of AM‐251 (0.5 mg/kg; P < 0.001). In conclusion, the present study for the first time reveals the possible role of opioid signalling in the antidepressant‐like properties of AM‐251 in a foot‐shock stress model.